2022
DOI: 10.7759/cureus.24873
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Infection Presenting as an Isolated Severe Acute Liver Failure

Abstract: The clinical features of severe acute respiratory syndrome-coronavirus disease 2019 (SARS-COVID-19) infection range from mild upper respiratory symptoms to severe acute respiratory failure. Among other less common features are diarrhea, nausea, vomiting, elevated liver enzymes, and acute kidney injury. We present a case of a 49-year-old female with no preexisting liver disease who presented with weakness and dizziness for one week. Initial investigations revealed acute liver failure (ALF) and positive COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, liver injury in COVID-19 has been noted to be transient, while hepatic biochemical tests return to normal within 2-3 wk[ 6 ]. Severe liver injury, with aminotransferases > 20 times ULN, has been observed in 0.1% of COVID-19 patients on admission and in 2% during hospitalization, while acute liver failure, induced by COVID-19, has been reported in extremely rare cases[ 27 , 28 ]. Febrile hepatitis, acute cholecystitis and hepatic artery thrombosis are, also, rare clinical presentations of COVID-19[ 29 - 31 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Furthermore, liver injury in COVID-19 has been noted to be transient, while hepatic biochemical tests return to normal within 2-3 wk[ 6 ]. Severe liver injury, with aminotransferases > 20 times ULN, has been observed in 0.1% of COVID-19 patients on admission and in 2% during hospitalization, while acute liver failure, induced by COVID-19, has been reported in extremely rare cases[ 27 , 28 ]. Febrile hepatitis, acute cholecystitis and hepatic artery thrombosis are, also, rare clinical presentations of COVID-19[ 29 - 31 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Several reports have highlighted the occurrence of liver enzyme abnormalities, acute hepatitis, and an ALF associated with SARS-CoV-2 infection [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. It has been documented that approximately 76.3% to 82.5% of COVID-19 cases display abnormal liver test results [ 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Sobotka et al indicated that severe acute liver injury (ALI) was infrequent, occurring in 0.1% of patients upon admission and 2% during hospitalization, with no ALF observed among a cohort of 1555 patients [ 30 ]. The available literature on ALF in the context of COVID-19 remains limited, with only a handful of reports documenting such cases [ 39 , 40 , 41 , 42 , 43 ]. The reports on ALF cases are provided in Table 2 , with the main findings summarized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with preexisting liver disease (LD) are more susceptible to disease deterioration during an infection, with COVID-19 being one of the most challenging ones [24]. However, this phenomenon was also noted in patients without previous liver dysfunction [25]. It has been postulated that an uncontrolled immune response with a high release of cytokines causing hyperinflammation and consequently multi-organ damage may be one of the possible causators [23].…”
Section: Discussionmentioning
confidence: 99%